Trichophyton rubrum is Inhibited by Free and Nanoparticle Encapsulated Curcumin by Induction of Nitrosative Stress after Photodynamic Activation - Baltazar, Ludmila Matos (PLoS One, 2015)
Antimicrobial photodynamic inhibition (aPI) utilizes radical stress generated from the excitation of a photosensitizer (PS) with light to destroy pathogens. Its use against Trichophyton rubrum, a dermatophytic fungus with increasing incidence and resistance, has not been well characterized. Our aim was to evaluate the mechanism of action of aPI against T. rubrum using curcumin as the PS in both free and nanoparticle (curc-np) form. Nanocarriers stabilize curcumin and allow for enhanced solubility and PS delivery. Curcumin aPI, at optimal conditions of 10 μg/mL of PS with 10 J/cm(2) of blue light (417 ± 5 nm), completely inhibited fungal growth (p<0.0001) via induction of reactive oxygen (ROS) and nitrogen species (RNS), which was associated with fungal death by apoptosis. Interestingly, only scavengers of RNS impeded aPI efficacy, suggesting that curcumin acts potently via a nitrosative pathway. The curc-np induced greater NO(•) expression and enhanced apoptosis of fungal cells, highlighting curc-np aPI as a potential treatment for T. rubrum skin infections.